Galidesivir, a Direct-Acting Antiviral Drug, Abrogates Viremia in Rhesus Macaques Challenged with Zika Virus. (4th October 2017) - Lim, So-Yon; Osuna, Christa; Lakritz, Jessica; Chen, Elsa; Yoon, Gyeol; Taylor, Ray; MacLennan, Steve; Leonard, Michael; Giuliano, Enzo; Mathis, Amanda; Berger, Elliot; Babu, Ys; et al.
Abstract: Background: Zika virus (ZIKV) was first isolated from a sentinel rhesus monkey in 1947. ZIKV infection in humans is associated with serious neurological and reproductive complications. No antiviral or protective vaccine is yet available. Galidesivir an adenosine analog is a potent viral RNA-dependent RNA polymerase inhibitor with demonstrated broad-spectrum antiviral activity. Methods: We have conducted four pre-clinical studies in rhesus macaques to assess the safety, antiviral efficacy and dosing strategies of galidesivir against ZIKV infection. Collectively, we have challenged 70 rhesus macaques by various routes using 1x10 5 TCID50 of a Puerto Rican ZIKV isolate. We have evaluated galidesivir therapy administered via IM injection as early as 90 minutes and up to 72 hours after subcutaneous (SC) ZIKV challenge, and as late as 5 days after intravaginal (IVAG) challenge. In these studies, we evaluated the efficacy of a range of loading and maintence doses of galidesivir. The highest dose evaluated has been a loading dose of 100mg/kg BID followed by a maintenance dose of 25mg/kg BID for nine days. We followed multiple endpoints, including ZIKV RNA levels in plasma, urine, saliva, and cerebrospinal fluid. Immune activation, complete blood counts, chemistries and galidesivir pharmacokinetics were also monitored. Results: Galidesivir was well-tolerated in all studies. All untreated controls developed high-level plasma viremia, and had readily detectable ZIKV RNA in CSF, saliva and urine post-infection. Animals treated in the first 24 hours after SC ZIKV challenge did not develop plasma viremia and were either negative or had significantly reduced ZIKV RNA in bodily fluids. Animals treated with galidesivir later (up to 72 hours) were partially protected; they had detectable plasma ZIKV RNA, but the onset was delayed and/or magnitude significantly reduced compared with controls. Animals infected IVAG were protected by galidesivir treatment up until day 5 after infection, with no blood viremia and significant reductions in ZIKV RNA in the CSF as compared with controls. Conclusion: Galidesivir dosing in rhesus macaques was well-tolerated and offered significant protection against ZIKV infection. These results warrant continued study and clinical evaluation. Disclosures: R. Taylor, BioCryst Pharmaceuticals: Employee, Salary; S. MacLennan, BioCryst: Employee, Salary; M. Leonard, BioCryst: Employee, Salary; E. Giuliano, BioCryst: Employee, Salary; A. Mathis, BioCryst Pharmaceuticals: Employee, Salary; E. Berger, BioCryst: Employee, Salary; Y. Babu, BioCryst: Employee, Salary; W. Sheridan, BioCryst Pharmaceuticals: Employee, Salary